2005
DOI: 10.1002/bip.20356
|View full text |Cite
|
Sign up to set email alerts
|

Cα‐Tetrasubstituted amino acid based peptides in asymmetric catalysis

Abstract: C(alpha)-tetrasubstituted alpha-amino acids constitute a powerful tool for controlling the conformation of short peptide sequences. Chiral peptides may be used in stereoselective reactions both for asymmetric induction and in kinetic resolution. By reviewing recent data from our own laboratories and by presenting new results on the stereoselective oxidation of chalcone to the corresponding oxide, this contribution shows that the control of peptide conformation is a critical issue in order to achieve successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Importantly, a strong correlation was observed between the rigidity of the b-hairpin structure and the enantioselectivity of the catalyst [9]. This hypothesis was confirmed by studies by Toniolo et al of related catalysts in which the b-turn inducing a-amino isobutyric acid (Aib) residue was replaced by other C a -tetrasubstituted amino acids [10]. Conformational analysis by 1 H-nuclear magnetic resonance (NMR) and Fourier transform infrared spectroscopy confirmed that the conformational constraint plays a key role in the enantioselectivity of the catalyst.…”
Section: Peptide Models Of Hydrolytic Enzymessupporting
confidence: 66%
See 3 more Smart Citations
“…Importantly, a strong correlation was observed between the rigidity of the b-hairpin structure and the enantioselectivity of the catalyst [9]. This hypothesis was confirmed by studies by Toniolo et al of related catalysts in which the b-turn inducing a-amino isobutyric acid (Aib) residue was replaced by other C a -tetrasubstituted amino acids [10]. Conformational analysis by 1 H-nuclear magnetic resonance (NMR) and Fourier transform infrared spectroscopy confirmed that the conformational constraint plays a key role in the enantioselectivity of the catalyst.…”
Section: Peptide Models Of Hydrolytic Enzymessupporting
confidence: 66%
“…Strategies that will be discussed are the use of small oligopeptides with a persistent secondary structure, the spontaneous self-assembly of simple peptidic fragments into large aggregates, and the incorporation of peptide fragments in multivalent structures such as dendrimers and nanoparticles. 10.2.1.1 Catalytically Active Peptide Foldamers Inspired by enzyme models, Miller et al started by embedding nucleophiles in conformationally restricted peptidic structures in order to discover catalysts for asymmetric acyl-transfer reactions [8]. Histidine residues served as nucleophiles in a series of b-turn-type peptides for the kinetic resolution of trans-(AE)-N-(2-hydroxycyclohexyl)acetamide.…”
Section: Peptide Models Of Hydrolytic Enzymesmentioning
confidence: 99%
See 2 more Smart Citations
“…49) On the other hand, Toniolo and co-workers reported asymmetric epoxidation 50) and oxidation reactions 51,52) using the helical secondary structures of a,a-disubstituted amino acid peptides. 53) The author has started to study the utilization of chiral cyclic a,a-disubstituted amino acids for drug design, and for the development of asymmetric reactions.…”
Section: Resultsmentioning
confidence: 99%